LEGAL FRAMEWORKS FOR SPECTRUM SHARING: UNLOCKING INDONESIA'S BROADBAND POTENTIAL - Kosasih, Achmad Arizki; Ramli, Tasya Safiranita; Virhani, Mohan Rifqo (Kanun Jurnal Ilmu Hukum, 2024)
This article analyzes the application of spectrum sharing regulations in mobile broadband technology in Indonesia. Since 2019, the country has witnessed significant progress in the widespread adoption of 4G LTE broadband network infrastructure. However, the development of 5G telecommunications technology remains nascent, operating in a non-standalone mode that relies on existing 4G LTE infrastructure and is currently available only in several major cities. To improve service quality and increase accessibility to 4G LTE and 5G broadband networks, a clear and comprehensive legal framework is essential. This framework should facilitate the sharing of 4G LTE infrastructure, particularly radio frequency spectrum, with 5G technology, thereby enhancing broadband coverage in underdeveloped, frontier, and outermost regions. The Indonesian government has enacted the Job Creation Law, which addresses spectrum sharing in the telecommunications sector. This research employs a normative juridical approach, integrating both primary and secondary data analysis to examine the legal framework governing spectrum sharing. It specifically investigates the impact of the Job Creation Law on the implementation of spectrum sharing in Indonesia's telecommunications landscape. The findings indicate that the current spectrum sharing policy is insufficiently supportive of 4G LTE technology, thereby impeding the deployment of 5G non-standalone technology in underdeveloped, frontier, and outermost areas. To remedy this situation, spectrum sharing policies must ensure non-discriminatory access, be responsive to market demands, and adapt to technological advancements. Moreover, the study highlights the importance of collaborative efforts among stakeholders in crafting spectrum sharing provisions that address the needs of both 4G LTE and 5G technologies.